Biochemical and molecular evaluation of jatropha meal as biofeed - Oskoueian, Ehsan (2012)
Jatropha curcas L. (J. curcas) plant is well known as a source of seed oil for biofuel production. The plant thrives well in tropical conditions and its planting acreage has increased considerably in Malaysia. In the process of oil extraction of the seed kernel, a residue called Jatropha meal is produced. The meal could be a potential biofeed due to its chemical and bioactive compounds present. However, the bioactive compounds present in the seeds differ among different genotypes of J. curcas plant. Thus, before considering the local Jatropha meal as a biofeed, it is imperative to determine the bioactive compounds and biological activities of the meal which would indicate its possible applications and limitations. It is also important to ascertain the J. curcas variety that is grown in Malaysia, is either toxic or non-toxic according to the profiles of the bioactive compounds present. Therefore, the hypothesis of this research was, the Jatropha meal is safe and has functional biofeed properties. In order to test the hypothesis a comprehensive study on the bioactive compounds and biological activities of Jatropha meal, physicochemical treatments, and how the meal and isolated phorbol esters from the meal affect rumen microbial activity were first conducted to evaluate the meal as a biofeed. This was followed by the cytotoxicity evaluation and mode of action elucidation of isolated phorbol esters from the meal on bovine kidney cell line. The results showed that chemical analysis of Jatropha meal obtained from local J. curcas plant contained 61.8% crude protein, 9.7% neutral detergent fibre and 4.8% acid detergent fibre. The meal also contained high levels of total phenolics (3.9 mg/g DM), total flavonoids (0.4 mg/g DM), total saponins (19 mg/g DM), phytic acids (9.1 %), trypsin inhibitors (34.2 mg/g DM), lectins (102.7 U)and phorbol esters (3.0 mg/g DM). The high performance liquid chromatography(HPLC) analyses of Jatropha meal showed the presence of gallic acid, pyrogallol, rutin, myricetin and daidzein with the values of 581.3±0.36, 631.1±0.47, 47.6±0.53,198.5±0.29 and 297.5±0.27 μg/g DM, respectively. The gas chromatography-mass spectrometry analyses (GC-MS) indicated the presence of other metabolites,including 2-(hydroxymethyl)-2-nitro-1,3-propanediol, β-sitosterol, 2-furancarboxaldehyde,5-(hydroxymethyl), furfural (2-furan carboxaldehyde) and acetic acid. The Jatropha meal methanolic extract, vitamin C, butylated hydroxytoluene (BHT) and β-carotene showed free radical (2,2-diphenyl-1-picrylhydrazyl) scavenging activity with the IC50 values of 1.6, 0.3, 0.3 and 1.5 mg/ml, respectively, while values for the ferric reducing power activity were 3.0, 0.3,0.3 and 2.6 mg/ml, respectively. Jatropha meal extract showed antibacterial activity against several pathogenic bacteria including Enterobacter aerogenes, Klebsiella pneumonia, Escherichia coli, Pseudomonas aeruginosa, Micrococcus luteus,Bacillus subtilis, Bacillus cereus, and Staphylococcus aureus with the in hibitionrange of 0.21-1.63 cm at the concentrations of 1 and 1.5 mg/disc. The Jatropha meal methanolic extract, at the concentration of 100 μg/ml, inhibited the inducible nitric oxide synthase in macrophages RAW 264.7, comparable to Nω-L-nitro-arginine methyl ester (L-NAME) indicating appreciable anti-inflammatory activity.Combinations of hydrothermal treatment, alkali and oxidizing agents alleviated the levels of phenolic compounds, saponin and phorbol esters significantly (p≤0.05), while the level of phytic acid did not decrease. Trypsin inhibitors and lectin activity were fully inactivated. The level of phorbol esters decreased by 76.7% on treatment with heat, 3% (w/w) NaOH and 10% (v/w) NaOCl. In vitro fermentation by rumen microbes showed a significant (p≤0.05) decrease in fermentation parameters when chemically treated meals were used as the substrates, while physically treated meals did not affect the fermentation parameters significantly. Effects of four different levels of isolated phorbol esters from Jatropha meal i.e., 3, 6, 9 and 12 mg/30 ml buffered rumen fluid, on rumen fermentation using ground Guinea grass as the substrate were studied in vitro. The results showed that apparent dry matter degradability, metabolisable energy, total volume of gas produced after 24 h of incubation (IVGP24) and total volatile fatty acids decreased significantly (P≤0.05) in treatments with 9 and 12 mg phorbol esters. Rumen microbial specific enzyme activity (CMCase, FPase, xylanase and β-glucosidase), purine content (index of rumen microbial protein) and rumen microbial protein synthesis showed a significant decrease (P≤0.05) on treatments with 9 and 12 mg phorbol esters. Similarly, the population of bacteria, fungi, protozoa, methanogens, archaea and major cellulolytic bacteria, including Fibrobacter succinogenes, Ruminococcus albus, R.flavefaciens and Butyrivibrio fibrisolvens, significantly (p≤0.05) decreased when 9 and 12 mg phorbol esters were added. The disappearance of phorbol esters upon rumen microbial fermentation was observed with values ranging from 23.0% to 44.1%. The in vitro toxicity evaluation of crude extract obtained from rumen fluid treated with phorbol esters before and after 24 h fermentation on viability of bovine kidney cells (MDBK) (ATCC: CCL-22) demonstrated a significant (p≤0.05) decrease in the toxic effect of the phorbol esters where the cell viability improved from 43.6% to 72.3%. The phorbol esters of Jatropha meal were isolated into four fractions namely, PE1, PE2, PE3 and PE4. In vitro cytotoxicity assay showed cells death with the CC50 values ranging from 52.4 to 109.6 μg/ml in bovine kidney cell line when exposed to all fractions of phorbol esters and using phorbol-12-myristate-13-acetate (PMA) as positive control upon 24, 48 and 72 h exposure. The isolated phorbol esters induced cell death in a dose and time dependent manner. The light microscope examination indicated no apparent changes in the morphology of the MDBK cells upon 12 h exposure to all phorbol ester fractions and PMA, while after 24 h exposure, significant morphological changes, detachment, destruction of cells and apoptotic bodies were seen. The expression of the PKC-β II gene from signal transduction pathway, c-Fos, c-Jun and c-Myc from proto-oncogenes, and IL-1β and Cox2 genes from inflammatory pathway, on 12 h treatment with isolated phorbol esters and PMA at the CC50 concentrations, showed significant (p≤0.01) overexpression in all of the genes, with values ranging from 1.3 to 5.1 fold increase as compared to the untreated cells. Western blot analysis also confirmed the gene expression results, and showed the significant (p≤0.01) overexpression of PKC-β II, c-Fos, c-Jun, c-Myc, Cox2 and IL-1β proteins, with values ranging from 1.48 to 3.15 fold increase as compared to the untreated cells. The flow cytometry results confirmed the apoptotic cell death in MDBK cells upon 24 h exposure to isolated phorbol esters and PMA. Consequently, the results of this study showed that the local J. curcas plant is of the toxic variety due the presence of phorbol esters, and although the meal could be considered as a potential biofeed, due to the presence of various biological activities and bioactive compounds, however, the cytotoxic effect of phorbol esters could not becompromised. Although the rumen microbes could detoxify the phorbol esters partially, it is still not sufficient to consider it safe as a biofeed due to their cytotoxic effects even at low concentrations. Therefore, complete removal of phorbol esters from Jatropha meal is absolutely necessary.